Influencia de la separación de residuos sólidos urbanos para reciclaje en el proceso de incineración con generación de energía - Poletto, José A. [UNESP]; Da Silva, Celso L. [UNESP] (My University, 2009)
This work analyses the recuperation of the energy of Municipal Solid Waste (MSW) through the incineration process. It considers the up to date tendency of segregation (separation) of plastic, paper and cardboard, glass and metals and their influence in the fluxes of mass and energy in the incineration system of MSW. For its development was used information related to the generation of MSW in Bauru city and the Combust software. The results so obtained allowed the estimation of the Caloric power of the typical MSW and also of this residue when one considers the separations of paper/cardboard and plastic for recycling.
Influence of the separation of municipal solid wastes to recycling in the incineration process with energy generation
Keywords: Calorific power; Energy generation; Incineration; RSU; Solid Wastes; Energy generations; Incineration process; Incineration systems; Municipal solid waste; Work analysis; Energy conversion; Recycling; Separation; Solid wastes; Waste incineration